Durable renal response and safety with add-on belimumab in patients with lupus nephritis in real-life setting (BeRLiSS-LN). Results from a large, nationwide, multicentric cohort. Issue 124 (November 2021) - Gatto, Mariele; Saccon, Francesca; Andreoli, Laura; Bartoloni, Elena; Benvenuti, Francesco; Bortoluzzi, Alessandra; Bozzolo, Enrica; Brunetta, Enrico; Canti, Valentina; Cardinaletti, Paolo; Ceccarelli, Fulvia; Ciccia, Francesco; et al.
Abstract: Background: Belimumab was recently approved for treatment of lupus glomerulonephritis (LN). Aim: To evaluate renal response and its predictors in LN patients receiving belimumab in real-life. Patients and methods: We considered all patients fulfilling the SLEDAI-2K renal items and/or having estimated glomerular filtration rate (eGFR)≤60 ml/min/1.73 m 2, with positive anti-dsDNA and/or low C3/C4 enrolled in the multicentre Italian lupus cohort BeRLiSS (BElimumab in Real LIfe Setting Study), treated with monthly IV Belimumab 10 mg/kg over standard treatment. Primary efficacy renal response (PERR), defined as proteinuria ≤0.7 g/24 h, eGFR≥60 ml/min/1.73 m 2 without rescue therapy, was considered as primary outcome. Complete renal response (CRR; proteinuria <0.5 g/24 h, eGFR≥90 ml/min/1.73 m 2 ) was considered as secondary outcome. Prevalence and predictors of PERR were evaluated at 6, 12, 24 months by multivariate logistic regression. Results: Among the 466 SLE patients of BeRLiSS, 91 fulfilled the inclusion criteria, 79 females, median age 41.0 (33.0–47.0) years, median follow-up 22.0 (12.0–36.0) months. Sixty-four (70.3%) achieved PERR, of whom 38.4% reached CRR. Among patients achieving PERR at 6 months, 86.7% maintained response throughout the follow-up. At multivariable analysis, hypertension (OR [95%CI]: 0.28 [0.09–0.89], p = 0.032), high baseline serum creatinine (0.97 [0.95–0.99], p = 0.01) and high baseline proteinuria (0.37, [0.19–0.74], p = 0.005) negatively predicted PERR. Positive predictors of PERR at 12 and 24 months were baseline anti-Sm positivity (OR [95%CI]: 6.2 [1.21–31.7], p = 0.029; 19.8 [2.01–186.7], p = 0.009, respectively) and having achieved PERR at 6 months (14.4 [3.28–63.6]; 11.7 [2.7–48.7], p = 0.001 for both). Conclusions: Add-on therapy with belimumab led to durable renal response in patients with LN in a real-life setting. Highlights: Belimumab is effective and safe as add-on therapy in LN in real-life. Higher baseline proteinuria hampers response and favors belimumab discontinuation. Early achievement of renal response upon belimumab heralds response durability.